Systematic Review: The Impact of Particulate Matter 2.5 (PM2.5) Exposure on Public Health Around Coal Mines - Putri Utami (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2025)
Air pollution is one of the major public health challenges in Indonesia. Coal mining areas are air polluted and vulnerable to air pollution, especially PM2.5 dust particles. Air pollution in coal mining areas if not managed can cause degradation of the atmospheric environment. The impact of unmanaged PM2.5 can cause harm to humans, especially respiratory health problems and even death. This article aimed to summarize several relevant scientific articles on the description of the impact of PM2.5 exposure on public health that occurs due to coal mining. This article used the systematic review method. The literature search used two scientific databases, namely Google Scholar and Science Direct published in the range of 2016-2024. There were 1133 articles retrieved in the initial selection, and at the end there were 10 articles included in the systematic review. Based on the review conducted on the selected articles, the results show that coal mining can have several negative impacts on the health of the surrounding community, which can cause various acute respiratory infections, asthma, coughing, Chronic Obstructive Pulmonary Disease (COPD), digestive disorders, cardiovascular disorders, and accumulation of PM2.5 that exceeds the threshold and in a long time can cause death.